2021
DOI: 10.5851/kosfa.2021.e2
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Listeria monocytogenes in Smoked Duck: Antibiotic and Heat Resistance, Virulence, and Genetics of the Isolates

Abstract: This study aimed at determining the genetic and virulence characteristics of the Listeria monocytogenes from smoked ducks. L. monocytogenes was isolated by plating, and the isolated colonies were PCR identified. All the obtained seven L. monocytogenes isolates possessed the virulence genes (inlA, inlB, plcB, and hlyA) and a 385 bp actA amplicon. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The published studies have reported the increasing of L. monocytogenes strains’ resistance to the entire range of antibiotics of different classes [ 27 , 32 , 35 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The study analysed resistance to 12 antimicrobial agents, and demonstrated that the analysed L. monocytogenes strains were susceptible to a considerable proportion of the analysed agents except clindamycin, meropenem, penicillin G, and trimethoprim/sulfamethoxazole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The published studies have reported the increasing of L. monocytogenes strains’ resistance to the entire range of antibiotics of different classes [ 27 , 32 , 35 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The study analysed resistance to 12 antimicrobial agents, and demonstrated that the analysed L. monocytogenes strains were susceptible to a considerable proportion of the analysed agents except clindamycin, meropenem, penicillin G, and trimethoprim/sulfamethoxazole.…”
Section: Discussionmentioning
confidence: 99%
“…Its mechanism of action is similar to that of erythromycin, i.e., it is responsible for the inhibition of protein synthesis due to the binding with the 50S subunit of bacterial ribosomes [ 49 , 56 ]. There are several studies indicating a high level of clindamycin resistance among the L. monocytogenes isolates derived from food and production facilities [ 45 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. According to studies conducted by Şanlıbaba et al, 2018 [ 49 ] and Escolar et al, 2017 [ 56 ], the strains’ resistance to clindamycin may be associated with the action of the clindamycin structure-modifying enzyme that contributes to the inactivation of the antibiotic action.…”
Section: Discussionmentioning
confidence: 99%
“…In meat, Pseudomonas, Acinetobacter, and Brochothrix mainly affect the quality and may cause spoilage (Liang et al, 2021;Wei et al, 2021). Also, Pathogenic bacteria such as E. coli, Salmonella, Campylobacter, L. monocytogenes, and S. aureus are frequently detected in meat (Kim et al, 2020;Lee and Yoon, 2021;Park et al, 2021;Yang et al, 2022). Spoilage yeasts mainly include Zygosaccharomyces, Saccharomyces, Candida and Brettanomyces, and spoilage molds include Zygomycetes, Penicillium, Aspergillus, etc.…”
Section: Mics Of Preservatives To Food Spoilage Microorganisms In Bro...mentioning
confidence: 99%
“…Listeria monocytogenes , Clostridium perfringens , Salmonella spp., and Escherichia coli are the main foodborne pathogens isolated from meat products ( Cetin et al, 2020 ; Chang et al, 2020 ; Park et al, 2021 ). Preservatives in foods can prevent the growth of spoilage bacteria and foodborne pathogens; thus, it is necessary to use preservatives in food manufacturing, particularly meat products.…”
Section: Introductionmentioning
confidence: 99%